THU0292 Stimulation of juvenile systemic lupus erythematosus blood cells induces IL-17 production. (23rd January 2014) - Ballantine, L.; Midgley, A.; Watson, L.; Beresford, M.
Abstract : Background: Th17 cells are a recently described subset of CD4 + cells characterised by the production the cytokines IL-17A, IL-17F and IL-22. This subset will differentiate from naïve T cells in the presence of IL-23, TGFβ, IL-1β and IL-6 under the control of the transcription factor RORC. The pathogenesis of adult-onset systemic lupus erythematosus (SLE) has been linked to Th17 cells due to reported increase in serum levels of IL-17 and an increased frequency of Th17 cells [1, 2]. However, there have been few investigations into the presence and role of Th17 cells within the more severe, juvenile-onset SLE (JSLE) phenotype. Objectives: The objective of this study was to investigate ability of JSLE peripheral blood mononuclear cells (PBMCs) to produce IL-17 protein production upon CD3/CD28 stimulation. In addition we analysed the level of Th17-associated cytokines within JSLE plasma and the mRNA levels of IL-17 associated proteins and transcription factors within JSLE and control patients. Methods: JSLE (n=4) and control (n=3) PBMCs were stimulated with CD3/CD28 activation beads at a 2:1 ratio for 2 days. After this period, cell-free supernatants were extracted and analysed by IL-17 ELISA. In addition, unstimulated PBMC RNA was extracted from JSLE (n=11) and control (n=10) patients. RT-PCR quantified levels of IL-17A, IL-23, IL-23R and RORC mRNA relative to RPL13A housekeeping gene. CD4 + T cells were isolated from JSLE (n=12) and control (n=10) patients and IL-17A mRNA levels were quantified. Plasma from JSLE (n=11) and control (n=5) were analysed for IL-17 levels. All results are displayed as mean±SEM. Results: JSLE CD3/CD28 activated PBMCs produced higher levels of IL-17 protein compared to control activated PBMCs (167.5 pg/ml ±146.4 vs 23.8 pg/ml ±11.9). IL-17A and IL-23 mRNA expression was significantly higher in JSLE PBMCs compared to controls (IL-17A: 0.30 (±0.08) vs 0.07 (±0.02) p=0.018; IL-23: 0.41 (±0.11) vs 0.34 (±0.254), p=0.042). RORC and IL-23R mRNA expression was also raised in JSLE compared to controls, although not statistically (IL-23R: 0.43 (±0.16) vs 0.16 (±0.07), p=0.189; RORC: 0.52 (±0.16) vs 0.3 (±0.13), p=0.218). CD4 + cells from JSLE patients expressed higher levels of IL-17A mRNA compared to control patient CD4 + cells (0.86±0.18 vs 0.51±0.13, p=0.081). IL-17A was undetectable in JSLE and control plasma. Conclusions: These data indicate Th17 cells may be playing a pathogenic role in JSLE as JSLE PBMCs are able to secrete IL-17 upon stimulation. The inability to find IL-17 in JSLE patient plasma suggests it may be expressed at site specific locations i.e. the kidneys. The higher level of IL-17 associated proteins and transcription factor mRNA in JSLE patients indicates the presence of the pro-inflammatory environment required for Th17 differentiation. References: Zhao, X.F., et al., Increased serum interleukin 17 in patients with systemic lupus erythematosus. Mol Biol Rep, 2010. 37(1): p. 81-5. Xing, Q., et al., Elevated Th17 cells are accompanied by FoxP3+ Treg cells decrease in patients with lupus nephritis. Rheumatol Int, 2011. Disclosure of Interest: None Declared